Change in Psychotherapy: A Dialogical Analysis Single-Case Study of a Patient with Bulimia Nervosa - Salvini, Alessandro; Faccio, Elena; Mininni, Giuseppe; Romaioli, Diego; Cipolletta, Sabrina; Castelnuovo, Gianluca (Frontiers in Psychology, 2012)
Starting from the critical review of various motivational frameworks of change that have been applied to the study of eating disorders, the present paper provides an alternative conceptualization of the change in psychotherapy presenting a single case study. We analysed six psychotherapeutic conversations with a bulimic patient and found out narratives “for” and “against” change. We read them in terms of tension between dominance and exchange in I-positions, as described by Hermans. These results indicate that the dialogical analysis of clinical discourse may be a useful method to investigate change from the beginning to the end of therapy.